(untitled) (Al-Academy, 2023)
The research entitled (The Visual Illusion in American Contemporary Ceramics) includes four chapters، the first chapter of which includes the methodological framework for the research، which contains the research problem focused on the following question: Has the American potter succeeded in achieving the artistic and aesthetic In the art of ceramics، as in the art of drawing and graphics، the fact that the art of ceramics has its advantages and limits in terms of material and technology? The aim of the research was to identify visual illusions in visual art in the works of a selected group of American potters. While the importance of the research was evident in that it sheds light on the methods and techniques of optical art in contemporary American ceramics While the research limits were limited to ceramic works including the United States of America and the temporal limits (2000-2020)، and the chapter was concluded by specifying the most important terms mentioned in the title of the research As for the second chapter، it is the theoretical framework for the research and it contain 2 paragraphs. The first is concept of visual illusion and the employment of visual illusion in the plastic arts. The second paragraph included the influence of the optical illusion style in contemporary ceramics As for the third chapter، the research included the research procedures. It included the research samples consisting of (4) American ceramics and The chapter included the descriptive analytical approach as a method of research، and the fourth and final chapter included From the research on the results of the research، the researcher provided a set of conclusions that emerged from the research